Capital Market Outlook: Assessing Opportunities and Risks in Stocks, Bonds and Mutual Funds Under Indonesia’s Macroeconomic Environment - M. Nuruddin Subhan; Shinta Budi Astuti; Riska Yustisiana; Bintang Andhyka; Wasi Widayadi; Fachri Affandi; Athia Zerlina (Universitas Pancasila, 2026)
The Indonesian capital market has experienced significant growth, with the number of registered investors increasing from 1.6 million in 2018 to more than 12 million in 2024. However, this growth has not been accompanied by a proportional increase in financial literacy. Based on the National Survey of Financial Literacy and Inclusion by OJK (2024), Indonesia’s financial literacy index has only reached 65.43%, while the financial inclusion index has reached 75.02%. This gap between financial access and financial capability highlights the importance of structured and evidence-based financial education at the community level.This paper reports the implementation of a Community Service Program (PkM) on Financial Literacy, conducted collaboratively by the Faculty of Economics and Business, Universitas Pancasila (FEB-UP), and Maahad Tahfiz Al-Quran Lil Muttaqin, Selangor, Malaysia. The program was conducted online via the Zoom platform on February 13, 2026, and was attended by 21 participants. Evaluation instruments in the form of pre-tests and post-tests were used to measure participants’ financial knowledge and behavior before the training, as well as to assess the effectiveness of the program after the training.The pre-test results indicated that the average participant knowledge score was 83%, while the financial behavior score was at a moderate level of 62%, with notable gaps in emergency fund provision (43%) and long-term asset investment (47%). The post-test evaluation results were highly positive, with an average overall satisfaction score of 4.78 out of 5.00 (96%), and all six evaluation indicators receiving ratings in the “Strongly Agree” category. Overall participant satisfaction reached a perfect score of 100%.These findings indicate that the program was effective in delivering financial literacy material to the target audience, and that the online training model proved to be accessible and impactful. It is recommended that the program be continued, expanded in scope, and developed as a replicable model for cross-border community service collaboration.